Pembuatan Trikalsium Fosfat Berpori Menggunakan Metode Protein Foaming-Starch Consolidation Dengan Variasi Penambahan Jumlah TCP Dalam Slurry Dan Kecepatan Pengadukan - Lia Yuningsih; Ahmad Fadli; Irdoni Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Tricalcium phosphate (TCP) has been widely used as a bone substitute material and teeth because it is biocompatible and similar to the mineral structure of human bone. Porous Tricalcium phosphate (TCP) was made by protein foaming-starch consolidation method by using egg white as a pore-forming agent and starch like sago flour as the consolidator. The purpose of this research is to study the effect of stirring rate and addition of TCP in slurry on the physical, chemical and mechanical properties of porous TCP. This research was began by mixing TCP, egg whites, starch and Darvan 821 A by certain composition and then stirred for 3 hours with stirring rate of 100.150 and 200 rpm. The slurry was poured into a mold and dried in an oven at 180oC for 1 hour. Then the samples removed from the mold to produce green bodies. Afterthat, the green bodies were burned at 600 oC and followed by sintering at 1100oC with rate of 2oC/min for 2 hours. This research result shows the porosity of porous TCP bodies increased with increasing stirring rate, but the compressive strength decreased. The addition of TCP in the body was found to increase the compressive strength when the porosity decreased . The TCP with a porosity of 66.67 to 72.77 % and 0,75 to 1,08 MPa compressive strength were found at stirring rate of 100 rpm. Meanwhile, the stirring rate of 200 rpm, the TCP has a porosity from 68,13 to 76,92% obtained 0.68 to 1 MPa compressive strength. Keyword : compressive strength, egg white, porosity,tricalcium phosphate